PENAMBAHAN DAUN BINAHONG (Anredera cordifolia) PADA PAKAN UNTUK MENINGKATKAN LAJU KELANGSUNGAN HIDUP IKAN NILA (Oreocromis nilaticus) - Robiyannor Robiyannor; Sri Herlina; Siti Norida; Mazlan Mazlan (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
Tilapia (Oreochromis niloticus) is a rapidly growing aquaculture commodity. However, in the process of tilapia farming, there are issues with low appetite and survival rates during the fry stage. Binahong leaves are a natural ingredient that can be used to improve fish appetite and health. This study aims to determine how powdered binahong leaf feed affects fish survival rates and tilapia feeding behavior. The study lasted 42 days. A descriptive analysis method was used, and the study consisted of three treatments. The immunostimulant treatments administered via feed were: A (Control) and B (Binahong Leaves at 125 g/kg feed). The primary parameters of this study were fish survival rate and feeding response. Supporting parameters included temperature, pH, and dissolved oxygen (DO). The results indicated that the addition of binahong leaf powder (Anredera cordifolia) in feed significantly increased the survival rate and feeding response of Nile tilapia (Oreochromis niloticus) by 100%—as no mortality occurred and the best feeding response was observed in treatment B, which included 125 g/kg of Binahong leaves (Anredera cordifolia) in the feed. The results obtained can be recommended as a natural immunostimulant in aquaculture feed.